2021
DOI: 10.1002/gj.4121
|View full text |Cite
|
Sign up to set email alerts
|

Maturity and thermal evolution differences between two sets of Lower Palaeozoic shales and its significance for shale gas formation in south‐western Sichuan Basin, China

Abstract: The Lower Cambrian Qiongzhusi shale and the Upper Ordovician-Lower Silurian Wufeng-Longmaxi shale are major source rocks and important shale gas exploration targets in the Sichuan Basin. Cutting and core samples from two shale gas wells in south-western Sichuan Basin have been selected for organic matter (OM) reflectance measurement and Raman spectra analysis with the aim to determine maturity. The results were incorporated for basin modelling to construct the thermal evolution of this area. Graptolite fragmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 100 publications
0
2
0
Order By: Relevance
“…The Luzhou area is located in the southeastern part of Sichuan, on the outskirts of the Sichuan Basin in the north and the gently sloping Yunnan-Guizhou Plateau in the south, and thus has both basin and hilly topography. During the study, it was also found that a paleo uplift trend began to evolve in southeastern Sichuan from the Indo-Chinese period onwards (Wang et al 2021), providing an excellent dynamic basis for the subsurface and surface resources (Potter 2018) of the later Luzhou region. The Luzhou region has developed topographic features of high south and low north, as well as various landform types and agrotypes, because of the continuous change and coupling of land masses.…”
Section: Ecological Environment Analysis In Luzhou Regionmentioning
confidence: 82%
“…The Luzhou area is located in the southeastern part of Sichuan, on the outskirts of the Sichuan Basin in the north and the gently sloping Yunnan-Guizhou Plateau in the south, and thus has both basin and hilly topography. During the study, it was also found that a paleo uplift trend began to evolve in southeastern Sichuan from the Indo-Chinese period onwards (Wang et al 2021), providing an excellent dynamic basis for the subsurface and surface resources (Potter 2018) of the later Luzhou region. The Luzhou region has developed topographic features of high south and low north, as well as various landform types and agrotypes, because of the continuous change and coupling of land masses.…”
Section: Ecological Environment Analysis In Luzhou Regionmentioning
confidence: 82%
“…However, it is difficult to accurately distinguish the OM particles in high-over thermal evolution shales due to their small size and similar optical properties. Liu et al [35] and Wang et al [42] carried out Raman spectroscopy experiments on different macerals in shales at the high-over-mature stage, but no significant difference was found in the results of different macerals. The consistency of results confirms that for the high-over-mature samples, Raman spectroscopy performed on kerogens can provide rapid estimates of equivalent vitrinite reflectance, and there is no need to distinguish different organic macerals.…”
Section: Introductionmentioning
confidence: 99%